2016
DOI: 10.1053/j.jvca.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Grading Aortic Stenosis With Mean Gradient and Aortic Valve Area: A Comparison Between Preoperative Transthoracic and Precardiopulmonary Bypass Transesophageal Echocardiography

Abstract: Objective: The authors hypothesized that average precardiopulmonary bypass (pre-CPB) transesophageal echocardiographic (TEE) mean gradient (PG m ) and aortic valve area (AVA) values would be significantly different from preoperative transthoracic (TTE) values in the same patients and that these changes would affect pre-CPB TEE grading of aortic stenosis (AS).Design: Retrospective, observational design. Setting: Single university hospital. Participants: The study comprised 92 patients who underwent aortic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…Based on the study, conducted by Whitener et al .,[7] considering average PGm as 46.0 in pre-induction TTE group and as 39.6 in pre-CPB TEE, with power as 90% and α error as 5%, sample size of 54 patients was derived. Thus, we decided to enroll 60 patients in our study with 30 in each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study, conducted by Whitener et al .,[7] considering average PGm as 46.0 in pre-induction TTE group and as 39.6 in pre-CPB TEE, with power as 90% and α error as 5%, sample size of 54 patients was derived. Thus, we decided to enroll 60 patients in our study with 30 in each group.…”
Section: Methodsmentioning
confidence: 99%
“…[6] In a retrospective, observational study preoperative TTE PGm and AVA values were compared with precardiopulmonary bypass (CPB) TEE, and it was found that preCPB TEE often underestimates AS severity. [7] The reason for this disparity is unclear. One of the reasons might be that AS grading was originally defined in spontaneously breathing patients.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic valve gradients decrease and calculated valve areas increase in the operating room. 21 Left ventricular outflow obstruction in hypertrophic cardiomyopathy frequently improves after induction produces a pharmacologic sympathectomy. 22 Finally, the myocardial depressant effects of inhalation agents affect echocardiographic measurements of ventricular performance.…”
Section: Color Doppler and Mitral Regurgitationmentioning
confidence: 99%
“…1,4 Previous research has shown that V p , PG m , and AVA obtained during precardiopulmonary bypass TEE often underestimates the severity of AS. 5 Additional research has shown that there is more discordance between mean PG m and AVA during precardiopulmonary bypass TEE than during preoperative TTE. 6 In a perfect world, one could perform a TEE examination and have certain parameters be in complete agreement with previously reported studies across all modalities.…”
mentioning
confidence: 99%
“…V p and PG m were more likely to underestimate AS severity, which confirmed previous work by this group. 5 So what is a cardiac anesthesiologist to do? Whitener et al again remind us that a comprehensive approach to assessment of AS is necessary and that no single parameter should be used alone.…”
mentioning
confidence: 99%